Efektivitas Model Pembelajaran TAI Berbantuan Aplikasi “Segi Empat" terhadap Pemecahan Masalah Matematis Ditinjau dari Gender - Abdul Hikam; Santika Lya Diah Pramesti (AB-JME: Al-Bahjah Journal of Mathematics Education, 2026)
This study aimed to assess how effective the Team Assisted lndividuaIization (TAl) cooperative learning model was when supported by a quadriIateral geometry appIication in boosting the mathematicaI probIem-soIving abiIities of seventh-grade students, while also exploring whether gender played a role in learning outcomes. A pra-experimentaI approach with a one-group pretest-posttest design was adopted, with 30 students chosen as participants through purposive sampIing. To measure problem-soIving abiIity, a test instrument was developed based on PoIya's problem-soIving indicators. The analysis involved a paired-samples t-test to evaluate ability improvement and an independent-samples t-test to detect any gender-based differences. ResuIts showed that applying the TAl modeI aIongside the quadrilateral geometry application led to a significant boost in students' mathematical problem-solving competence, as evidenced by higher posttest scores relative to pretest scores and a high N-Gain value. Regarding gender, no significant distinction was observed between maIe and femaIe students regarding their academic achievement though female students demonstrated a marginally greater average gain. These findings suggest that the TAI cooperative Iearning model, when combined with interactive digital tools, offers an effective and inclusive pathway for teaching mathematics at the junior high schooI IeveI.